Pembelajaran Berdiferensiasi Dalam Konteks Ilmu Pengetahuan Alam Di SMP: Kajian Literatur - Ratna Sari Titin Prihatini (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research aims to review and analyze the literature related to the application of differentiated learning in the context of Natural Science in Junior High School (SMP). Differentiated learning is an approach that pays attention to individual student differences in the teaching and learning process, by providing variations in methods, materials, and assessments. This literature review will discuss the concepts, principles, and benefits of differentiated learning, as well as its application in learning Science at the junior high school level.